THE SPECIFICS OF INTERACTION AND COMMUNICATION IN THE EDUCATIONAL SPHERE OF TECHNOLOGICAL SOCIETY (SOCIO-PHILOSOPHICAL ANALYSIS) - Chenbai, Natalia (Proceedings of the National Aviation University Series Philosophy Cultural, 2024)
Introduction. To achieve self-realization, a person of the 21st century needs to obtain a quality education that will provide opportunities for self-improvement. In forming a new educational paradigm, educators of social and humanitarian disciplines have faced new challenges. This necessitated a socio-philosophical study of the peculiarities of communication and interaction in the educational sphere of a technological society. Aim and tasks is to identify the peculiarities of communication and interaction in the field of education in the context of the formation of a new educational paradigm. Research methods for achieving this goal include socio-cultural and systemic approaches, as well as methods of analysis, synthesis, and hermeneutics. Research results. In the global society, the problem of moving from opposing an individual's values to realizing their unity with others is becoming particularly acute. When it comes to teaching, communication becomes the main factor that influences the entire process of teaching and upbringing of young people. Communication through dialogue is a prerequisite for the further development of education in the context of the realities of a technological society. Discussion. In modern philosophical and scientific discourses, education is seen as a means of overcoming natural communication barriers between people. As a new educational paradigm takes shape, a key principle of reformers at all levels is to recognize the subjectivity and mutual tolerance of all participants. Conclusions. The use of the sociocultural context in communicative interactions will contribute to the disclosure of the student's identity and will shape his ability to understand other people, which, ultimately, will help create a holistic personal picture of the world.